PECULIARITIES OF PEDAGOGICAL VISION FEOKTIST HARTAHAYEM THE PROCESS OF TEACHING LANGUAGES IN POLISH GYMNASIUMS OF THE SECOND HALF OF THE XIX CENTURY - I.V. Sharovarina (Academy of Cognitive and Natural Sciences, 2007)
The language teaching methodology can be defined as the comparative methodology based on synthetic means taking into account perceptual psychology, teaching approach in native language, linguistic translating, mechanical and intentional reading.